Google Classroom Training in Supporting Online Learning During the COVID-19 Pandemic at Bimbingan Belajar Hudallinnas - Nasution, Winda Suci Lestari; Nusa, Patriot; Nasution, Koprawi (Talenta Publisher, 2022)
This year the world is experiencing a COVID-19 pandemic, so educators are witnessing the development of technology in all fields, including in the field of education. During the COVID-19 pandemic, educators must be brave in taking steps to make online learning an opportunity to transform education. There are several steps that can be considered together in transforming education, especially regarding online learning. The purpose of this service is to take this step by sharing knowledge regarding online learning methods which are currently very much needed during the COVID-19 pandemic by making e-learning training based on virtual classes with Google Classroom as a learning medium in Hudallinnas tutoring. Google Classroom is an internet-based service provided by Google with an e-learning system. So that it can be used as an efficient, effective and interactive learning media to support technology-based learning. Hudallinnas Tutoring plays a role in maintaining the continuity of learning so that it continues to run well during the pandemic. While the method used is the practical training method through the transfer of knowledge through training and simulations of Google Classroom application training which are carried out virtually with the hope of achieving equitable abilities in understanding and mastering the Google Classroom application to support online learning with the aim of increasing and increasing the knowledge and abilities of students. educators in using the Google Classroom application so that online learning activities can run effectively.